Trends and innovations in cucumber root-knot nematode disease control - Jianhui, Go; Hasnain, Hussain; Bingtai, Wang; Jie, Ma; Qingshan, Yang (Springer Nature, 2025)
Root-knot nematode is one of the main diseases of cucumbers, and it seriously affects the quality, quantity, and yield of cucumbers. With the continuous development of science and technology, under the influence of agricultural sustainable development, the control strategies of the cucumber root-knot nematode are also changing. In this review, a visual bibliometric analysis is used to understand the research history, current situation and development trend of cucumber root-knot nematode disease. The CiteSpace software analysed 420 research articles on cucumber root-knot nematode in the Web of Science (WoS) database from 1973 to 2024 and conducted inductive statistics from the author, country, institution and keywords. The analysis showed that the number of articles has consistently increased since 2011, peaking in 2023. China and the United States are the leading contributors, with the largest number of publications and relatively concentrated research institutions. International collaborative research efforts have commenced but require further enhancement. The Crop Protection and the Journal of Nematology have published the highest number of articles, but fewer articles were published in high-impact journals. In terms of content, research on cucumber root-knot nematodes has evolved from traditional field prevention and control to investigations into resistance mechanisms, leveraging molecular biology techniques and grafting methods to enhance cucumber’s self-resistance to root-knot nematodes. Biological control is currently a prominent research topic, with existing measures primarily focusing on antagonistic microorganisms and plants for safer and more effective multidisciplinary integration, representing the future direction of cucumber root-knot nematode research.